Genomics Reference Resource for African Cattle (GRRFAC) - Marshall, Karen; Hanotte, Olivier H.; Tijjani, Abdulfatai (2023)
The Genomic Reference Resource for African Cattle (GRRFAC) initiative is aiming at harnessing the genetic resources of indigenous cattle breeds across Africa. These resources are yet to be tapped and are prerequisite for a complete characterization of local breeds diversity towards genetic improvement, contributing to food security and poverty reduction on the continent. Our aim is to catalogue the entire functional diversity, including SNPs and structural variations, by collating up to 1000 whole-genome sequences and genotype information of African indigenous cattle (both in public and newly generated one). Our current objectives include the identifications of the most informative SNPs for designing the African cattle reference SNP genotyping arrays to be applied to breeding improvement programs and the genomic regions underpinning adaptation and productivity traits, as well as the capacity building among African collaborating scientists through training in bioinformatics and genomics, thereby paving the way towards a complete genome characterisation of African indigenous cattle diversity for breeds improvement. Key words: African cattle, genetic improvement, adaptation, production, genomic characterization, The Genomic Reference Resource for African Cattle (GRRFAC) initiative is aiming at harnessing the genetic resources of indigenous cattle breeds across Africa. These resources are yet to be tapped and are prerequisite for a complete characterization of local breeds diversity towards genetic improvement, contributing to food security and poverty reduction on the continent. This unprecedented research effort is one of the Centre for Tropical Livestock Genetics and Health (CTLGH) Dairy Genomics project, being achieved through an extensive collaboration of African national partners with ILRI Livestock Genetics program, supported by the Roslin Institute at the University of Edinburgh (UK), Scotland Rural College (UK), University of Nottingham (UK), ILRI - CAAS Joint Laboratory on Livestock and Forage Genetic Resources (China) and Seoul National University (South Korea). A collated set of sequence and genotype information on African indigenous cattle breeds for use by the African and international research community in cattle genomics for the ultimate benefit of African livestock keepers, other livestock value chain actors and animal-source food consumers.